Factors Influencing Employees’ Loyalty Evidence from Nepalese Corporations - Gyawali, Bishnu Prasad (Management Dynamics, 2020)
Emerging world has entered into economic globalization and the information era where the business sector is now facing the ever-growing pressure from domestic and overseas competitors. More and more employers start to realize that customer loyalty depends on employee loyalty. They really understand happy loyal committed employees make for happy loyal committed customers who continue to buy the industry’s products and services. The aim of this study is to explore the factors influencing the employees’ loyalty in the Corporations. This research had been conducted to examine the important factors influencing employees’ loyalty towards pay benefits, work environment, organization culture and value and training and development opportunities. This study has used descriptive and analytical research design taking both primary and secondary data. The results show that higher employee loyalty is related to their nature of work, career advancement and recognition, relationship with their supervisors and working environment. Though employee loyalty towards the Corporations is observed positive in the study, the Corporations has unable to build loyalty in terms of employment benefits. The result of this study is useful for effective human resource management in Nepalese context.